Analysis of Quality of Work Life and Job Satisfaction of Nurses at Regional Public Hospital of West Tulang Bawang - Virya Wijayati (Enrichment : Journal of Management, 2021)
This study aimed to describe the level of quality of work life and job satisfaction of nurses at Regional Public Hospital of West Tulang Bawang. This study used the descriptive analytic method. It took a saturated sample where the entire population was used as the research sample with a total of 82 nurses at the Regional Public Hospital of West Tulang Bawang per March 2021. Primary data were collected from questionnaires, which were subsequently analyzed using SPSS 20. The results of this study indicate that the level of quality of the work life of nurses at the Regional Public Hospital of West Tulang Bawang is at a good level with an average value of 3.74 based on the dimensions of work life-home life, work design, work context, and work world. Meanwhile, the level of job satisfaction of nurses at the Regional Public Hospital of West Tulang Bawang was at a poor level with an average value of 3.69 based on the dimensions of external rewards, schedule flexibility, family-work balance, coworker relationships, work environment interactions, opportunities to develop professionalism, praise and recognition, and control and responsibility.